Towards a Territorialised Professional Identity: The Case of Teaching Staff in Rural Schools in France, Spain, Chile and Uruguay - Rothenburger, Catherine (2015)
Rural schools have constituted a renewed subject of research since the 1980s, at both national and international levels. Small rural schools in France, Spain, Chile and Uruguay have points in common in terms of their organization (multi-year) and the implication of local participants. The immersion of teachers in the rural territory and their confrontation with a multi-year structure tend to upset their professional identity and often damage their «capacity system» (Costalat-Founeau, 1997). This study shows that teachers engage in numerous professional and personal activities both directed at the territory on a quest of social validation by the latter. By re-balancing their capacity system, they modify their representation of their own profession and thus their whole professional development. They gradually construct a territorialized professional identity and educational offer.